Bandwidth Optimization of a Wideband Co-Co Antenna Array on a Thin Flexible Dielectric using HFSS® - Joseph D. Majkowski , (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This paper presents several novel techniques for designing a compact Co-Co antenna array for optimal performance over a broad frequency range of one and half octaves. The antenna was modeled and tested on 6 mil Polyimide composite, a thin, flexible, substrate, in order to meet size requirements. A slotting technique was used to increase both the impedance and gain bandwidth of the antenna. The final design produced an omnidirectional antenna with peak gain greater than 1 dBi and S(1,1) less than -8 dB over a frequency range of 2.8*F1. In order to make a manufacture-able antenna, the microstrip transmission line width was increased for co-axial feeding of the antenna with a second slotting technique.